2022
DOI: 10.3390/molecules27051715
|View full text |Cite
|
Sign up to set email alerts
|

Change in Secondary Metabolites and Expression Pattern of Key Rosmarinic Acid Related Genes in Iranian Lemon Balm (Melissa officinalis L.) Ecotypes Using Methyl Jasmonate Treatments

Abstract: The medicinal herb, lemon balm (Melissa officinalis L.), which is high in rosmarinic acid (RA), has well-known therapeutic value. The goals of this study were to investigate the effects of methyl jasmonate (MeJA) on RA content, total phenolic content (TPC), and total flavonoid content (TFC), as well as changes in expression of their biosynthesis-related key genes (MoPAL, Mo4CL, and MoRAS) in Iranian lemon balm ecotypes, as first reported. Our results revealed that MeJA doses significantly increase the RA conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 64 publications
6
14
0
Order By: Relevance
“…In other words, our results suggest that 150 µM MeJA enhances the quantity of linalool present in various ecotypes of coriander, and that these elicitors have an impact on the expression patterns of genes involved in linalool production. Moreover, our results are consistent with those of other researchers [ 23 , 41 , 42 ] and imply that linalool levels in coriander plants vary according to genotype and dosage. Some research showed that the high levels of linalool seen following treatments with 100–150 µM MeJA represented the ideal dosage for treating various plant families [ 38 , 39 , 42 ].…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…In other words, our results suggest that 150 µM MeJA enhances the quantity of linalool present in various ecotypes of coriander, and that these elicitors have an impact on the expression patterns of genes involved in linalool production. Moreover, our results are consistent with those of other researchers [ 23 , 41 , 42 ] and imply that linalool levels in coriander plants vary according to genotype and dosage. Some research showed that the high levels of linalool seen following treatments with 100–150 µM MeJA represented the ideal dosage for treating various plant families [ 38 , 39 , 42 ].…”
Section: Resultssupporting
confidence: 93%
“…Moreover, MeJA treatments boosted the TFC levels in the Zanjan ecotype, which were around 1.70, 2.37, 3.73, and 2.66 times higher than the levels in untreated plants ( Figure 3 B). These findings support the findings of other studies [ 23 , 41 ] and demonstrate that TPC and TFC variations in coriander leaves depend on ecotype. Additionally, in all ecotypes under consideration, TPC values in both untreated and all treated leaves were greater than the TFC values, which is consistent with previous results [ 23 , 41 , 42 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations